Impact of fluoroquinolone cascade reporting of urine samples on antibiotic prescribing rates in a network of urgent care clinics. Issue 1 (20th June 2022) - Weichman, Brittani M.; Bushman, Amanda M.; Rogers, Kathie L.; Rosa, Rossana
Abstract: Cascade reporting is an antimicrobial stewardship strategy that has been successfully implemented in inpatient settings, but evidence of its impact on outpatient settings is scarce. We report on the impact on fluroquinolone prescribing at a network of urgent care clinics following the implementation of cascade reporting of Enterobacterales in urine cultures.